2012
DOI: 10.2332/allergolint.10-oa-0290
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profiles in Japanese Patients with Chronic Rhinosinusitis

Abstract: This study is thought to be the first one that showed the cytokine profiles in Japanese CRSs/wNP similar to those of European CRS. Based on mediator profiles, we suggest that CRSsNP and CRSwNP are distinct disease entities within the group of chronic sinus diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 26 publications
2
35
2
2
Order By: Relevance
“…It is widely accepted that the cytokine expression in the paranasal mucosa of CRSwNP patients differs from that of CRSsNP patients [6, 12, 13]. In fact, nasal polyp tissue, when compared with adjacent inflammatory nasal mucosa, was shown to express higher levels of IL-5 and lower levels of TGF-β mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely accepted that the cytokine expression in the paranasal mucosa of CRSwNP patients differs from that of CRSsNP patients [6, 12, 13]. In fact, nasal polyp tissue, when compared with adjacent inflammatory nasal mucosa, was shown to express higher levels of IL-5 and lower levels of TGF-β mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The cytokine profile of the ethmoid sinus mucosa and nasal polyps in ECRS or chronic rhinosinusitis with nasal polyp (CRSwNP) patients has been reported previously. Ethmoid sinus mucosa of CRSwNP patients showed significantly increased expression of interleukin (IL)-5, eosinophil-cationic protein, immunoglobulin E (IgE), and Staphylococcus enterotoxin (SAE)-IgE compared with chronic rhinosinusitis without nasal polyp (CRSsNP) patients [5, 6]. Ethmoid sinus mucosa of ECRS patients also showed significantly elevated expression of inducible nitric oxide synthase (iNOS) and IL-5 [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic rhinosinusitis with nasal polyps patients have higher mucosal IL-5 protein levels compared with chronic rhinosinusitis without nasal polyps patients. 12 Moreover, in chronic rhinosinusitis with nasal polyps patients, IL-5 protein levels are reported to be higher in allergic nasal polyps compared with non-allergic nasal polyps. 13 The present study found a significant decrease in blood eosinophils in eosinophilic chronic rhinosinusitis patients after surgery, along with a reduction in serum IL-5 level.…”
Section: Discussionmentioning
confidence: 99%
“…Non-eosinophilic inflammation is common in Chinese CRSwNP patients (28). The difference in endotypes is not associated with only racial differences; in a previous study, the cytokine profiles in Japanese patients with CRSwNP were found to be similar to those of European patients with CRS (29).…”
mentioning
confidence: 99%